The anti‐hypertensive drug prazosin inhibits glioblastoma growth via the PKCδ‐dependent inhibition of the AKT pathway. Issue 5 (4th April 2016) - Assad Kahn, Suzana; Costa, Silvia Lima; Gholamin, Sharareh; Nitta, Ryan T; Dubois, Luiz Gustavo; Fève, Marie; Zeniou, Maria; Coelho, Paulo Lucas Cerqueira; El‐Habr, Elias; Cadusseau, Josette; Varlet, Pascale; Mitra, Siddhartha S; et al.
Abstract: A variety of drugs targeting monoamine receptors are routinely used in human pharmacology. We assessed the effect of these drugs on the viability of tumor‐initiating cells isolated from patients with glioblastoma. Among the drugs targeting monoamine receptors, we identified prazosin, an α1‐ and α2B‐adrenergic receptor antagonist, as the most potent inducer of patient‐derived glioblastoma‐initiating cell death. Prazosin triggered apoptosis of glioblastoma‐initiating cells and of their differentiated progeny, inhibited glioblastoma growth in orthotopic xenografts of patient‐derived glioblastoma‐initiating cells, and increased survival of glioblastoma‐bearing mice. We found that prazosin acted in glioblastoma‐initiating cells independently from adrenergic receptors. Its off‐target activity occurred via a PKCδ‐dependent inhibition of the AKT pathway, which resulted in caspase‐3 activation. Blockade of PKCδ activation prevented all molecular changes observed in prazosin‐treated glioblastoma‐initiating cells, as well as prazosin‐induced apoptosis. Based on these data, we conclude that prazosin, an FDA‐approved drug for the control of hypertension, inhibits glioblastoma growth through a PKCδ‐dependent mechanism. These findings open up promising prospects for the use of prazosin as an adjuvant therapy for glioblastoma patients. Synopsis: Prazosin, an FDA‐approved drug for hypertension with a record of over 40 years of safe and effective clinical use, curbs intracranial glioblastoma growth in mice in a preclinical setting and is thus as a potential anti‐glioblastoma adjuvant drug. Prazosin induces glioblastoma cell apoptosis. PKCδ‐dependent inhibition of AKT pathway is identified as a possible mechanism for prazosin‐induced glioblastoma apoptosis, independently of adrenergic receptors. Glioblastoma growth in orthotopic xenograft mouse models was inhibited by prazosin and, as a consequence, mice survival increased. Abstract : Prazosin, an FDA‐approved drug for hypertension with a record of over 40 years of safe and effective clinical use, curbs intracranial glioblastoma growth in mice in a preclinical setting and is thus as a potential anti‐glioblastoma adjuvant drug.